The adventures of Tom Sawyer - Twain, Mark, 1835-1910. (Morristown, N.J. : Silver Burdett Co., 1982)
The adventures of a boy growing up in the nineteenth century in a Mississippi River town. Includes study guide.
"Study guide [by] Milton A. Kaplan": p. 1-49 (2nd group).
Reprint. Originally published: London : Chatto & Windus, 1876.
Bibliography: p. 46-47 (2nd group).
Keywords: Mississippi River -- Fiction; Missouri -- Fiction